2014
DOI: 10.1088/0004-6256/148/2/25
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Perturbations of the Galilean Satellites During Planetary Encounters

Abstract: The Nice model of the dynamical instability and migration of the giant planets can explain many properties of the present Solar System, and can be used to constrain its early architecture. In the jumping-Jupiter version of the Nice model, required from the terrestrial planet constraint and dynamical structure of the asteroid belt, Jupiter has encounters with an ice giant. Here we study the survival of the Galilean satellites in the jumping-Jupiter model. This is an important concern because the ice-giant encou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…As expected (cf. Deienno et al 2014), they are mostly near-parabolic due to strong gravitational focusing. The resemblance of the distribution of i enc (measured in the Neptunian-centric frame, see below) to a sine function suggests that the encounters are nearly uniformly distributed in the solid angle.…”
Section: Modelmentioning
confidence: 99%
“…As expected (cf. Deienno et al 2014), they are mostly near-parabolic due to strong gravitational focusing. The resemblance of the distribution of i enc (measured in the Neptunian-centric frame, see below) to a sine function suggests that the encounters are nearly uniformly distributed in the solid angle.…”
Section: Modelmentioning
confidence: 99%
“…Finally, it is also important to discuss three other aspects: (i) as the instability depicted in this work requires a relatively long sequence of Jupiter's jumps, it is important to check that a long phase of close encounters between Jupiter and pl5 does not destabilize the regular satellite system of Jupiter . Deienno et al (2014) concluded that what is important for the stability of the satellites is not the total number of encounters, but the distance of the closet one. Following Deienno et al (2014), the orbits of the Galilean satellites can be profoundly affected if the encounter distance (d enc ) between Jupiter and pl5 is d enc < 0.03 au.…”
Section: Mechanism Of Excitationmentioning
confidence: 99%
“…Deienno et al (2014) concluded that what is important for the stability of the satellites is not the total number of encounters, but the distance of the closet one. Following Deienno et al (2014), the orbits of the Galilean satellites can be profoundly affected if the encounter distance (d enc ) between Jupiter and pl5 is d enc < 0.03 au. They found that, 0.03 au < d enc < 0.05 au causes only small perfectly the constrains imposed and well representing Jupiter's current inclination.…”
Section: Mechanism Of Excitationmentioning
confidence: 99%
“…The orbital alignment of the Uranian moon systems suggests a "collisional tilting scenario" (Morbidelli et al 2012) and implies significant bombardment of the young Uranus. A combination of these observations constrains the migration of the giant planets (Deienno et al 2011), planet-planet encounters (Deienno et al 2014), bombardment histories (Levison et al 2001), and the properties of the early circumsolar disk (Jacobson and Morbidelli 2014). The Pluto-Charon system can be considered a planetary binary rather than a planet-moon system, since its center of mass is outside the radius of the primary, at about 1.7 Pluto radii.…”
Section: Introduction -Why Bother About Moons?mentioning
confidence: 99%